Comportamiento de los agregados de Bogotá ante cargas cíclicas - Caicedo, Bernardo (2007)
The results of an experimental work on three road granular materials from La Sabana de Bogotá are presented. These works include small strains precision triaxial tests under cyclic loading with measurement of the negative pore water pressure (suction). The influence of different initial conditions of density, water content and fines content was studied. The interpretation of the results, in the quasi-elastic domain, is based on total stress and effective stress analyses , the latter allowing to take into account the effects of both total stresses and negative pressure, in the perspective of a more rational design of pavement layers.